2018
DOI: 10.1177/0391560318766822
|View full text |Cite
|
Sign up to set email alerts
|

The role of blood neutrophil count and the neutrophil-to-lymphocyte ratio as a predictive factor for prostate biopsy results

Abstract: Neutrophil count and neutrophil-to-lymphocyte ratio cannot be predictive factors for positive prostate cancer biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…25 On the other hand, there are some other studies advocating that NLR cannot be used as a PCa marker. 27,28 In our study, NLR was found to be an insignificant parameter on logistic regression analysis for the diagnosis of PCa in patients with a PI-RADS 3 lesion and a PSA of < 10 ng/mL.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…25 On the other hand, there are some other studies advocating that NLR cannot be used as a PCa marker. 27,28 In our study, NLR was found to be an insignificant parameter on logistic regression analysis for the diagnosis of PCa in patients with a PI-RADS 3 lesion and a PSA of < 10 ng/mL.…”
Section: Discussionmentioning
confidence: 56%
“…Literature indicates that the association between NLR and PCa remains controversial. [26][27][28] Huang et al evaluated 662…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that inflammation had a role in the development of prostate cancer. Kawahara et al, (2015) in a retrospective study reported that the higher the N/L ratio the higher the incidence of prostate cancer as did Adhyatma et al, (2019), while that of Kamali et al, (2018) did not find an association. Our prospective study did not find an associated with clinically significant prostate cancer, and the predictive value was significantly inferior to that of PSA density, free percent PSA and primary CPCs.…”
Section: Discussionmentioning
confidence: 91%
“…ADHYATMA K P et al con rmed NLR has a promising performance in predicting PCa in patients with PSA above 4 ng/dL [16]. However, Kamali K et al found that neutrophil count and neutrophil-to-lymphocyte ratio cannot be predictive factors for positive prostate cancer biopsy [17]. A retrospective analysis study by Oh JJ et al found that NLR may be a potentially useful clinical marker in the detection of prostate cancer among men with a PSA level in the 4-10 ng ml-1 range.…”
Section: Discussionmentioning
confidence: 99%